Foundation leisure and tourism - Sutherland, Jon.; Canwell, Diane (London : Hodder and Stoughton, 1996)
This book is divided into three parts: Providing service to customers; Preparing visitor information materials; and Investigating working in the leisure and tourism industries.
Keywords: Tourism; Great Britain; Tourism -- Great Britain; Leisure industry -- Great Britain